An Interesting and Rare Case of Urachal Adenocarcinoma Enteric Type with Review of Literature - P Manjusha Mullappali; Sandhya Sundaram; Lawrence D Cruze; S Rajendiran; T Chandru (Journal of Clinical and Diagnostic Research, 2019)
The urachus is a tubular structure that connects the bladder and allantois in the embryonic development, which involutes after third trimester. Urachal tumours are extremely rare and accounts of about 0.3-0.7% of all the bladder malignancies. We report here a case of 65-year-old male who was a known case of type II Diabetes, presented with complaints of haematuria for one and a half month. On abdominal ultrasonography and computed tomography, showed a pedunculated mass measuring 3×2 cm in the bladder wall protruding into the bladder. Cystoscopy was done, a papillary growth was noted in the dome of the bladder. Cystoscopically guided biopsy was done which showed enteric type adenocarcinoma. The surgical specimen showed urachus adenocarcinoma of enteric type Stage IIIA in the Sheldon System. This case has six months of follow-up without any recurrence or metastasis.